KMT2A-rearranged acute lymphoblastic leukemia in infants: current progress and challenges - Janine Stutterheim; Inge M. van der Sluis; Kirsten S. Vrenken; Rob Pieters; Ronald W. Stam (Haematologica)
Chromosomal translocation of the KMT2A gene represents the cytogenetic hallmark of acute lymphoblastic leukemia diagnosed in infants (